2012
DOI: 10.1021/jp309832u
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Gel to Fluid Phase Transformation in Unilamellar DPPC Vesicles

Abstract: The dynamics of the gel to fluid phase transformation in 100 nm large unilamellar vesicles (LUV) of 1,2-dipalmitoyl(d62)-sn-glycero-3-phosphocholine (d62-DPPC), has been studied by laser-induced temperature-jump initiation coupled with time-resolved infrared spectroscopy and by MD simulations. The infrared transients that characterize the temperature dependent phase transformation are complex, extending from the nanosecond to the millisecond time scales. An initial fast (submicrosecond) component can be modele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The presence of gD in the sample increases the rate of the phase transition; at 1°C from the T m , the rate of the transition is ∼3.5-fold faster. Previous transient studies have also reported timescales consistent with critical behavior (6,24). At the high temperatures (T f = 30°C and 34°C), τ relax increases ( Fig.…”
Section: Significancesupporting
confidence: 68%
See 2 more Smart Citations
“…The presence of gD in the sample increases the rate of the phase transition; at 1°C from the T m , the rate of the transition is ∼3.5-fold faster. Previous transient studies have also reported timescales consistent with critical behavior (6,24). At the high temperatures (T f = 30°C and 34°C), τ relax increases ( Fig.…”
Section: Significancesupporting
confidence: 68%
“…2 A and B shows the kinetics for peak B of the ester groups for DMPC vesicles with and without gD over a 9°C range above T m : T f = T m + 1,6,10°C. Previous experiments on lipid vesicles, using a variety of probes, have found evidence of multiple relaxation timescales, and a dependence on the particular probe used (6,(22)(23)(24)(25). To address this uncertainty about the dynamics present, how they may depend on vibrational frequency, and which functional form is appropriate to describe the kinetics, we first used a maximum entropy (MaxEnt) method to determine the inverse Laplace transform (ILT) of the kinetic traces and obtain the underlying distribution of rates as a function, shown in Fig.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies have been carried out in the context of biologically relevant lipids, typically diglycerides with functionalized headgroups such as dipalmitoylphosphatidylcholine (DPPC) [31,[33][34][35]37,38,41,42,45,47]. However, these lipids remain relatively challenging to simulate, owing to difficulties in the force-field design [50,51] and treatment of electrostatic interactions [50,[52][53][54][55][56][57], and to the slow convergence of system properties with respect to both system size [18,[49][50][51][58][59][60] and simulation timescale [18,58,[61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…At a given temperature, a lipid bilayer exists in either liquid or solid phase. 24,25,[29][30][31][32][33] The solid phase is commonly referred as a gel phase. The characteristic temperature unique for each lipid defines the transition from the gel to the liquid phase.…”
Section: Introductionmentioning
confidence: 99%